A Rare Case of Acute Purulent Myopericarditis Due To Klebsiella Pneumoniae: Challenge in Diagnosis and Management - Pertiwi, Gusti Ayu Riska; Amijaya, Agus Gowinda; Maliawan, Rani Paramitha Iswari (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Background: Acute purulent myopericarditis due to Klebsiella pneumoniae is an uncommon condition in the current era of widespread antibiotic use. The condition can lead to rapid fluid buildup around the heart, causing cardiac tamponade and sepsis, both of which can be life-threatening. The typical manifestation of myopericarditis may be absent and possess significant challenges in diagnosis and treatment. Imaging techniques can detect pericardial effusion or inflammation, but it cannot identify the exact cause. Early diagnosis and treatment are essential to improve patient outcomes. This article was conducted to report a case of acute purulent myopericarditis caused by Klebsiella pneumoniae that is barely reported. Case Summary: A male, 52 years old, presented with prolonged fever, progressive dyspnea and palpitation. The physical and supporting examination only showed the clinical symptoms of thyroid storms, heart failure, and coronary artery disease. Acute purulent myopericarditis was developed three days after therapy, proven by echocardiography, laboratory, and myopericardial fluid analysis. Purulent mixed hemorrhagic fluid was evacuated from pericardiocentesis with positive culture for Klebsiella pneumoniae sensitive to ceftriaxone. Ceftriaxone, ibuprofen, and colchicine were given. Constrictive pericarditis was found, so surgical pericardiectomy was performed. The patient showed significant clinical and echocardiographic improvement, discharged in stable condition. Conclusion: Myopericarditis should always be kept in mind as differential diagnosis in patient with pericardial effusion and when it rapidly deteriorated, purulent bacterial infection although rare could be the possible cause. Prompt intervention through fluid evacuation, adequate antibiotic therapy and surgical pericardiectomy when indicated, were needed to improve disease outcome -- Highlight: 1. A rare case of purulent myopericarditis caused by Klebsiella pneumoniae presented with atypical features, leading to diagnostic challenges in a patient with multiple comorbidities. 2. Early recognition, multimodal imaging, and prompt intervention—including pericardiocentesis, antibiotics, and surgical pericardiectomy—proved lifesaving and highlight the importance of individualized management in such rare infections.